2006
DOI: 10.1039/b518332d
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular photosynthetic triad of slipped cofacial porphyrin dimer, ferrocene, and fullerene

Abstract: A supramolecular triad consisting of self-assembled imidazolyl-zinc-porphyrin dimer, ferrocene, and fullerene was successfully constructed, resulting in long-lived charge separated species after efficient photoinduced electron transfer and charge shift reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…139 The heterogeneously organized dimer was covalently linked and then isolated. In the organized triad 89·90, electron transfer from the slipped-cofacial dimer to the fullerene as electron acceptor occurred 10 times faster than the succeeding hole shift to the terminal ferrocenyl group.…”
Section: A Charge-separation In Donor-acceptor Systemsmentioning
confidence: 99%
“…139 The heterogeneously organized dimer was covalently linked and then isolated. In the organized triad 89·90, electron transfer from the slipped-cofacial dimer to the fullerene as electron acceptor occurred 10 times faster than the succeeding hole shift to the terminal ferrocenyl group.…”
Section: A Charge-separation In Donor-acceptor Systemsmentioning
confidence: 99%
“…The assembly was fixed by means of ring-closing metathesis, and showed a long-lived Fc + -{Zn(porph)} 2 -C 60 C À charge-separated state upon photoexcitation. [93] Furthermore, the heterodimerization of 40 Zn-44 Zn with an indium tin oxide (ITO)-linked imidazolylporphyrin, followed by fixation by olefin metathesis, furnished systems that generated anodic photocurrents. [92] Fluorescence quenching was also observed for tricationic porphyrin 46, which is functionalized with a ferrocene unit covalently attached by a phenylethyl ether spacer.…”
Section: Photosynthetic Mimicsmentioning
confidence: 99%
“…bearing at least one acid chloride group in meso position [48,[65][66][67][68][69][70][71][72][73][74]. An inverse approach, which leads to similar molecular structures, involves the use of chlorocarbonyl-; 1,1 -bischlorocarbonyl-or [4-(chlorocarbonyl)phenyl]-ferrocene with meso(4-aminophenyl)-or meso(4-hydroxyphenyl)porphyrins [75][76][77][78][79]. A representative ferrocene-porphyrin-fullerene sequence synthesized by Imahori et al [73] to achieve long distance charge separated states is shown in Fig.…”
Section: Linkage Through Saturated Spacersmentioning
confidence: 99%